Digital Leadership In Madrasah - Pusvyta Sari; Laili Lailatul Hidayah; M. Chotibuddin; Nashihin (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2025)
Digital leadership characteristics are needed in developing digital madrasahs. With these characteristics, various obstacles are faced so that the digitalization transformation process can be carried out. This study was conducted to determine the principal’s characteristics at MA Ma'arif Almuhtadi, Paciran, Lamongan, East Java. This madrasah has succeeded in winning the digital madrasah innovation award. The study was conducted with a qualitative approach. Data collection was carried out using interview, observation and documentation techniques. The data collected is explained and concluded descriptively. The results of this study indicate that the principal of MA Ma'arif Almuhtadi has digital leadership characteristics. He is capable to think to face change, creative, visionary, has motivation to learn and has deep insight so that he can make decisions in complex situations. Digitalization programs in madrasah management can be carried out despite facing various obstacles. The role of digital leadership is very important to realize digital madrasahs effectively and efficiently.